Indicaciones para la realización del cultivo de mycobacterium tuberculosis como método diagnóstico de tuberculosis pulmonar y extra pulmonar. - Novillo Vicuña, Michael Dustin (Machala : Universidad Técnica de Machala, 2015)
Tuberculosis, contagious disease caused by mycobacteria of Mycobacterium tuberculosis complex (M. hominis , M. bovis , M. africanum) It is estimated that in 2014 contracted the disease 9 million people , the diagnosis of tuberculosis is suspected by the epidemiological radiológico clinician picture but should be confirmed by identification of Mycobacterium tuberculosis. In Ecuador three sputum tests are performed to respiratory symptoms , which 80% of pulmonary tuberculosis was diagnosed , the remaining 20 % must be intended for diagnosis by culture since despite being an expensive and time consuming method (2 , 8 weeks) is the gold standard in the diagnosis and management of TB patients presenting excellent specificity and sensitivity as a diagnostic test.
Tuberculosis, contagious disease caused by mycobacteria of Mycobacterium tuberculosis complex (M. hominis , M. bovis , M. africanum) it is estimated that in 2014 contracted the disease 9 million people , the diagnosis of tuberculosis is suspected by the epidemiological radiológico clinician picture but should be confirmed by identification of Mycobacterium tuberculosis. In Ecuador three sputum tests are performed to respiratory symptoms , which 80% of pulmonary tuberculosis was diagnosed , the remaining 20 % must be intended for diagnosis by culture since despite being an expensive and time consuming method (2 , 8 weeks) is the gold standard in the diagnosis and management of TB patients presenting excellent specificity and sensitivity as a diagnostic test.
Keywords: MYCOBACTERIUM; TUBERCULOSIS